Utilizing Online Resources for Speaking and Listening Skills: Teachers' Perspectives in Bangladeshi Context. - Shorna, Sadia Afrin; Suchona, Iffat Jahan (Jurnal Bahasa Inggris Terapan, 2024)
In this digital era, teachers are often required to employ successful methods like using the web as a type of technology to manage classrooms effectively. This research aims to explore how Private university-based English language teachers perceive the use of websites to help students improve their English listening and speaking skills. This study is based on phenomenological qualitative research and uses a method that looks at education and technology from different perspectives. The participants (18) were chosen from five private universities in Dhaka, Bangladesh. Semi-structured interviews with English language teachers were conducted to collect the data. The findings and analysis showed that using relevant websites and specific content to teach speaking and listening in English can accelerate students speaking and listening skills, as they are motivating and exciting and can help practice the skills inside and outside the classroom.